PENGEMBANGAN MODEL MITIGASI BENCANA BANJIR ROB DI KELURAHAN KANDANG PANJANG, KOTA PEKALONGAN (ANALISIS KAPASITAS DAN KERENTANAN AKTOR PADA MITIGASI BENCANA BANJIR ROB): - Nurul Hidayah; , Hanantyo Sri Nugroho (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This study examines the development of a tidal flood disaster mitigation model. Meanwhile, the theory used is John Twigg's theory, which is a systematic approach to identify, assess and reduce disaster risk. Therefore, this research is about the capacity and vulnerability of actors in disaster mitigation policies. This research method uses a qualitative descriptive research method. The results of the study show that Pekalongan City has a high level of tidal flood hazard. The area affected by the tidal flood hazard is Kandang Panjang Village, North Pekalongan District. The form of the stages of adaptation action for disaster risk reduction by the people in Pekalongan City against tidal floods, namely after the disaster and when the disaster occurred. The concept of mitigating tidal floods or reducing the risk of tidal floods in Kanjang Panjang sub-district, Pekalongan City has an impact on capacity and vulnerability. In addition, tidal floods in Pekalongan City are exacerbated due to high rainfall and small drainage. Based on the explanation above, it can be concluded that the recommendation for the development of a tidal flood disaster mitigation model in the Cage Panjang Village, Pekalongan City is non-structural.